Design of Microstrip Meander Line Antenna for Frequency Resonance 332 MHz on Portable ILS/VOR Receiver for Navigation Aids - Sianipar, Juan Ronaldo; Wildan, Muh.; Firmansyah, Teguh (Indonesian Journal of Education and Mathematical Science, 2024)
The Portable ILS/VOR Receiver (PIR) device is used for conducting Ground Inspection activities. The PIR antenna has traditionally employed a long-dimensioned dipole antenna. The design of the microstrip meander line antenna aims to reduce the antenna's dimensions for easy portability with the PIR device. The microstrip antenna is designed for Glidepath equipment in the frequency range of 328,6 MHz – 335,4 MHz, centered around 332 MHz. With antenna dimensions of 150 mm x 50 mm, simulation results indicate that the microstrip meander line antenna meets the desired standard specifications. At the center frequency of 332 MHz, it achieves a return loss of -19,65 dB, VSWR of 1,23. Bandwidth of 7 MHz and impedance of 48,94 Ω. Moreover, it exhibits an omnidirectional radiation pattern.